Pendekatan Islam dalam Pembangunan Ekonomi: Satu Konsep Menuju Kesejahteraan Umat - Syamsuri, Syamsuri (IAIN Ponorogo, 2019)
Abstract: Islam as a universal system of life always provided a humane solution (humanistic) based on the values in the Qur'an and the Hadith. Islam does not distinguish between the world and the hereafter, but Islam sees life as a single entity where the end of goal is to get lull of Allah SWT. . Therefore, the objective of the Islamic economic system is the perfect well-being in spirit as well as the bodies; welfare brings peace and inner enacting. Then in the concept of economic development considering multy-dimensions, that is the balance between material and spiritual, qualitative and quantitative, external and internal, including the moral aspect that maintains the status of man is not degrading to the level of slave development. Finally, this article try to explain that the model of economic development for the people to prosperity is by making religion and morality as the basis of its main. In the implementation of Islamic economic development must be based on seven principles; that is Islamic worldview as guideline to development, human beings as agents of development, the spirit world, the natural world and the hereafter as the time scale of development, science of fard 'ain as a frame of development, worship as the basis of development, natural resources as development tools, mardhotillah is the end of goal of development. الملخص: يوفر الإسلام كنظام حياة عالمي دائمًا حلولًا إنسانية تستند إلى القيم الموجودة في القرآن والحديث. الإسلام لا ينفصل بين الحياة الدنياوية والأخروية، ولكن الإسلام يرى الحياة كوحدة هدفها النهائي هو تحقيق رضا الله سبحانه وتعالى، بحيث يكون هدف النظام الاقتصادي الإسلامي هو الرفاهية المثالية روحيا وجسديا على حد سواء، الازدهار الذي يجلب السلام بين كل من الظاهر والداخلي، وبالمثل في مفهوم التنمية الاقتصادية الذي يرى من أبعاد مختلفة، وبالتحديد التوازن بين المادي والروحي، النوعي والكمي، الخارجي والداخلي، بما في ذلك الجوانب الأخلاقية التي تحافظ على الوضع الإنساني بدلاً من الإهانة إلى مستوى تنمية الخادم. سيحاول هذا المقال شرح نموذج واحد للتنمية الاقتصادية نحو رفاهية الشعب، أي وضع الدين والأخلاق كأساس رئيسي. في تنفيذ التنمية الاقتصادية الإسلامية يجب أن تقوم على سبعة مبادئ، هي النظرة الإسلامية العالمية كدليل للتنمية، والبشر كوكلاء للتنمية، وعالم الروح، والطبيعة العالمية ومقياس ما بعد الحياة كمقياس زمني للتنمية، و فرض عين كإطار ، والعبادة كأساس للتنمية، والموارد الطبيعية مثل أدوات التنمية، مرضاة الله تعالى هو الهدف النهائي للتنمية. Abstrak: Islam sebagai sistem kehidupan yang universal senantiasa memberikan solusi yang manusiawi (humanistic) berdasarkan nilai-nilai yang terkandung di dalam al-Quran maupun hadith. Islam tidak mendikotomi antara dunia dengan akherat, akan tetapi Islam melihat kehidupan sebagai satu kesatuan yang tujuan akhirnya adalah mengapai keredhaan Allah SWT... Sehingga objektif dari sistem ekonomi Islam adalah kesejahteraan yang sempurna baik itu secara ruh maupun jasad, kesejahteraan yang membawa ketenangan secara zahir maupun batin. Begitu halnya dalam konsep ekonomi pembangunan yang melihat dari berbagai dimensi yaitu keseimbangan antara material dan spiritual, kualitatif dan kuantitatif, eksternal maupun internal, termasuk aspek moral yang mempertahankan status manusia bukan merendahkan derajat ke tingkat hamba pembangunan. Artikel ini akan mencoba menjelaskan satu model pembangunan ekonomi untuk menuju kesejahteraan umat yaitu dengan cara meletakkan agama dan akhlak sebagai dasar utamanya. Dalam pelaksanaannya pembangunan ekonomi Islam harus berdasarkan pada tujuh prinsip yaitu worldview Islam sebagai pedoman pembangunan, manusia sebagai pelaku pembangunan, alam roh, alam dunia dan alam akhirat sebagai skala waktu pembangunan, ilmu fardhu ‘ain sebagai bingkai, ibadah sebagai dasar pembangunan, sumber alam sebagai alat pembangunan, mardhotillah merupakan tujuan akhir dari pembangunan.